The Comparison of Coronary Angiographic Profile between Diabetic and Non-Diabetic Patients with Coronary Artery Disease in a Nepalese Population - Katuwal, P.; Kattel, V.; Shrestha, N.R.; Maskey, R.; Karki, P. (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Background: Diabetes mellitus is associated with an increase in cardiovascular morbidity and mortality. As the prevalence of diabetes mellitus is increasing globally the burden of death related to cardiovascular disease including myocardial infarction will be a great burden to countries like Nepal. The aim is to compare the extent and severity of coronary artery disease between diabetic and non-diabetic patients referred for coronary angiography. Materials and methods: It was a Hospital-based, cross-sectional study conducted in the Department of Internal medicine, BPKIHS Dharan, Nepal. All consecutive patients undergoing coronary angiography with a clinical indication for the procedure during the study period of one year were included in the study. 61 subjects with diabetes were compared with 147 subjects without diabetes for assessing the severity and extent of coronary artery disease. The coronary atherosclerosis score was used to grade the severity of lesions visualized by coronary angiography. Results: The mean coronary atherosclerosis score was 6.64±4.18 among diabetes and 4.97±4.07 among the non-diabetic group with p-value of 0.008 which was statistically significant. The left anterior descending coronary artery was significantly more frequently involved in diabetics than nondiabetic patients 88.52% vs. 66.67% (p<0.002). Conclusion: Diabetic patients had more severe and extensive atherosclerotic lesions in coronary arteries than the non-diabetic patients on coronary angiography suggesting atherosclerotic burden in the diabetes population is higher in our population.